Methodology of criminal judiciary in developing the legal rule - Saeed, Israa; Ibraheem, Jamal (Journal of Legal Sciences, 2022)
Every mental action has a clear approach resulting from a sequence of thinking towards the goal to be achieved, and in order that the legal rule - to be developed - finds its acceptance by the highest degree criminal courts, and in order that it is adopted by the legislator, the criminal judge should adopt a certain methodology that matches his work. The developed judge is the one who keeps trying to harmonize the text with the new reality, and by doing this he may oppose the direction of the higher courts, but he convinces them through all the mental procedures and processes to show a “truth” on which the best solutions can be built.